Acute effects of yoga on short-term memory of physically active older adults - Matamoros Sánchez, Maribel Rocío (2023)
Introduction: It has been demonstrated that physical activity improves cognitive processes in older adults. Purpose: Evaluate acute effects of a Hatha Yoga class on short-term memory for physically active adults 60 years and older. Methodology: Nineteen elderly individuals (69.16 ± 6.82 years old) completed two 30-min sessions following a repeated measures design: one control session and one Hatha Yoga session. Short-term memory was assessed in both sessions pre and posttest (5-minutes after intervention). A Two-Way Repeated Measures ANOVA and simple effect analysis were computed. Results: A significant interaction between experimental condition and assessment was obtained (F=9.00; p=0.008). The simple effect analysis yielded a significant reduction in short-term memory in control condition between pre-test and post-test (F=6.02; p<0.05). Conclusion: A Hatha Yoga class lasting 30 min did not cause an acute effect on short-term memory in physically active adults 60 years and older. In addition, short-term memory seems affected after 30 min of rest, specifically, lying down.